Could Sex/Gender Differences in ACE2 Expression in the Lungs Contribute to the Large Gender Disparity in the Morbidity and Mortality of Patients Infected With the SARS-CoV-2 Virus? - Majdic, Gregor (Frontiers in Cellular and Infection Microbiology, 2020)
COVID-19 morbidity and mortality have significant gender disparities, with higher prevalence and mortality in men. SARS-CoV-2 enters the lungs through the ACE2 enzyme, a member of the renin-angiotensin system (RAS). Although there are no data for the lung, the expressions of RAS components in other tissues are modulated by sex hormones, androgens, and estrogens. However, there are no data on sex-specific differences in ACE2 expression. If there is a sex difference in the expression of ACE2 in the lung, this could theoretically explain the gender disparity in COVID-19 disease. More importantly, although modulation of ACE2 will certainly not provide a cure for the COVID-19 disease, modulation of ACE2 by sex hormone modulators, if they affect the expression of ACE2, could potentially be developed into a supportive therapy for COVID-19 patients.